Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1976
DOI: 10.1017/s0003356100035601
|View full text |Cite
|
Sign up to set email alerts
|

Effects of restricting the water intake of dairy cows upon their milk yield, body weight and blood composition

Abstract: SUMMARY1. Water intake was measured in eight lactating cows. Subsequently n i an experiment of a 4 × 4 Latin square design, each cow received 100, 87, 73 and 60% of its voluntary intake for 6 days followed by an 8-day recovery period.2. Measurements were made of the intake of feed, milk yield and quality, water, Na and K balances, metabolic profiles, and serum and urine osmolalities. The cows were weighed at the beginning and end ofthe experimental periods, and pulse, respiration and rumination rates and recta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
14
1

Year Published

1986
1986
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(20 citation statements)
references
References 12 publications
(9 reference statements)
3
14
1
Order By: Relevance
“…Therefore, it is not surprising that there were no differences in milk yield or milk composition between the treatment groups. These results agree with the findings reported by Little et al (1976), where water intake was restricted for a period of 6 d, and a second report (Little et al, 1978) of water restriction during a 3-wk period. In both experiments, milk yield was lowered by limiting water supply but was unaffected during the first 24-h period of water restriction.…”
Section: Discussionsupporting
confidence: 92%
“…Therefore, it is not surprising that there were no differences in milk yield or milk composition between the treatment groups. These results agree with the findings reported by Little et al (1976), where water intake was restricted for a period of 6 d, and a second report (Little et al, 1978) of water restriction during a 3-wk period. In both experiments, milk yield was lowered by limiting water supply but was unaffected during the first 24-h period of water restriction.…”
Section: Discussionsupporting
confidence: 92%
“…Cattle that normally eat 7.6 kg/day of feed ate 4.2, 2.2, 0.9 and 0.5 kg on four successive days when water was removed totally (Weeth et al, 1967). Little et al (1976) reported that a reduction of 40% in the amount of water allowed to dairy cows over a period of 6 days resulted in 16% reduction in feed intake. These show some similarities in the physiological adaptation of goats and cattle.…”
Section: Discussionmentioning
confidence: 99%
“…When multiple models had similar likelihood values, the model associated with the least Bayesian information criteria was chosen as the best prediction model. All the meta-analyses were Castle and Watson, 1973;Castle and Thomas, 1975;Little et al, 1976;Holter et al, 1982;Murphy et al, 1983;Stockdale and King, 1983;Andersson et al, 1984;Woodford et al, 1984;Andersson, 1985;Janicki et al, 1985;Nocek and Braund, 1985;Richards, 1985;Anderson, 1987;Gorewit et al, 1989;Holter et al, 1990Shalit et al, 1991;Bahman et al, 1993;Dado and Allen, 1993, 1995, 1996Silanikove et al, 1997;Dahlborn et al, 1998;Dewhurst et al, 1998;Muller et al, 1994;Mooney and Allen, 1997;Burgos et al, 2001;Osborne et al, 2002aOsborne et al, , 2009Voelker and Allen, 2003;Cottee et al, 2004;Meyer et al, 2004;Taylor and Allen, 2005;Harvatine and Allen, 2006;Chaiyabutr et al, 2007Chaiyabutr et al, , 2008Thomas et al, 2007;Cardot et al, 2008;Kume et al, 2008Kume et al, , 2010Longuski et al, 2009;Kramer et al, 2009;…”
mentioning
confidence: 99%